Diffuse Alveolar Hemorrhage Caused by Warfarin after Rifampicin Discontinuation - Takashige Kiyota; Seiji Shiota; Ryosuke Hamanaka; Daisuke Tsutsumi; Takeshi Takakura; Eishi Miyazaki (Case Reports in Medicine)
An 83-year-old man under warfarin therapy presented for assessment of prolonged prothrombin time and cough. High-resolution computed tomography findings of the chest showed diffuse alveolar hemorrhage. His international normalized ratio (INR) was 11.89. He had been treated with rifampicin for a persistent infection, but this had been discontinued about two months before admission. Rifampicin suppresses the anticoagulant activity of warfarin, which can lead to a need for increased doses of warfarin to achieve and maintain a therapeutic INR. More frequent INR monitoring is needed even after discontinuing rifampicin.